2001
DOI: 10.3171/foc.2001.11.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications with costotransversectomy and anterior approaches to thoracic and thoracolumbar tumors

Abstract: Object Anterior decompression and stabilization for thoracic spinal tumors often involves a thoracotomy and can be associated with surgical approach–related complications. An alternative to thoracotomy is surgery via a costotransversectomy exposure. To delineate the risks of surgery, the authors reviewed their prospective database for patients who had undergone surgery via either of these approaches for thoracic or thoracolumbar tumors. The complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 66 publications
(80 reference statements)
1
33
0
Order By: Relevance
“…Anterior-only approaches were comparable to posterior approaches in terms of EBL (475 vs 500 ml); however, anterior-posterior approaches had significantly higher EBL than the posterior approach (2500 vs 500 ml). Wiggins et al 18 reported on 47 patients, with 29 undergoing costotransversectomies and 18 undergoing thoracolumbar or combined approaches. They did not find a significant difference in complication rates between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior-only approaches were comparable to posterior approaches in terms of EBL (475 vs 500 ml); however, anterior-posterior approaches had significantly higher EBL than the posterior approach (2500 vs 500 ml). Wiggins et al 18 reported on 47 patients, with 29 undergoing costotransversectomies and 18 undergoing thoracolumbar or combined approaches. They did not find a significant difference in complication rates between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Class III evidence was provided by the 3 retrospective studies. In a retrospective comparison study, Wiggins et al 35 evaluated outcomes after performing 29 PCTs (Group 1) and 18 thoracolumbar or combined approaches (Group 2) as initial operations for thoracic neoplasms. The outcomes reported were mean Frankel grade at discharge (4.1 vs 4.7, respectively, p = 0.74) and mean ASIA motor score at discharge (90.4 [range 50-100] vs 98.3 [range 75-100], respectively, p = 0.04).…”
Section: Costotransversectomymentioning
confidence: 99%
“…These papers provided results on neurological outcomes, survival, recurrence, pain, and complication rates. There was 1 prospective cohort trial, 32 1 retrospective case-control study, 35 and 2 retrospective case series. 11,23 Class I evidence on the use of PCT was not available from any of the selected articles.…”
Section: Costotransversectomymentioning
confidence: 99%
See 2 more Smart Citations